Validation and measurement invariance of the Langer mindfulness scale: the Turkish version - Uysal Saraç, Menekşe; Yıldırım, Yıldız; Eşici, Hasan; Büyüköztürk, Şener; Pagnini, Francesco; Langer, Ellen (Frontiers in Psychology, 2024)
Novel distinction-drawing is an active process that characterizes mindfulness, which has been associated to an open, creative, and probabilistic mental state as well as the result of examining information from new perspectives. In the literature review, it was seen that there is no measurement tool for measuring mindfulness from a social and cognitive perspective in Türkiye. In addition, the frequent use of LMS in educational contexts and its adaptation to many languages have revealed the need to adapt the scale. The aim of this research is to validate the Turkish version of 14-item Langer Mindfulness Scale (LMS). The Turkish version's factorial structure was tested using the results of confirmatory factor analysis (CFA), which confirmed a three-factor structure that included the engagement, novelty producing, and novelty seeking subscales. It was found that measurement invariance based on gender was provided by LMS scores. LMS Turkish version showed satisfying psychometric properties in terms of reliability. Additionally, in this validation study, both convergent and discriminant validity were examined to provide evidence for criterion-based validity. For this purpose, the relationships between Turkish LMS's scores and positive and negative affect, openness to experiences, self-acceptance, self-defined humor and health were determined. The results showed that self-defined humor, positive affect, openness to experience, and self-acceptance were significantly positively correlated with the Turkish LMS scores. LMS scores and negative affect have a significant negative relationship. The findings suggest that the Turkish version of LMS, with its three dimensions, shows acceptable psychometric properties for assessing the state of mindfulness. The Turkish version of the LMS is expected to be used in socio-cognitive mindfulness research in a Turkish cultural context.